A new era in democratic Portugal? The 2009 european, legislative and local elections - Freire, A. (South European Society and Politics, 2010)
The main objective of this article is to analyse the campaigns and results of the three 2009 Portuguese elections: European, legislative and local. The 2009 election cycle also revealed some significant changes in the party system format (especially in the first two elections) which might have major consequences for the functioning of the political system, especially if the results are not merely short term and continue in future legislative elections, signalling a major change in the democratic model with a return to the kind of policies typical of the consensual period and away from the kind of policies typical of majoritarian one.